Bank fraud : using technology to combat losses - Subramanian, Revathi (Hoboken, New Jersey : John Wiley and Sons, Inc, 2014)
Offers a compelling narrative that ultimately urges security and fraud prevention professionals to make the most of the data they have so painstakingly gathered. Such professionals shouldn′t let their most important intellectual asset data go to waste. This book shows you just how to leverage data and the most up-to-date tools, technologies, and methods to thwart fraud at every turn.
Includes bibliographical references and index.
oif 15/06/15
Loan
Keywords: Banks and banking -- Security measures; Bank fraud -- Prevention; Bank fraud -- Prevention -- Technological innovation; Finance